My favorite mistake eaudiobook - Parker, Weston (Bad Boy Greeks, 2020)
I'd make a terrible father. That's what they all said. And it's the lie I lived for a long time, playing the field. Sleeping around and enjoying my life as a bachelor. But things change when my grandfather passes and all of his money comes my way. Life looks like a day in a theme park, with me as the big winner. Until I realize my grandfather didn't just send me a check, but also his big house filled with expensive art. Unfortunately, it comes with the responsibility of maintaining his staff, including a beautiful American maid that's driving me mad. I have rules about romance with those who work with me and for me. No bother. This curvy vixen wants nothing to do with me anyway. Until she does. And when I think it's going to be a quick fling, I'm shocked to discover she's carrying my greatest fear and the one thing I've always secretly wanted more than anything else. A baby. Contains mature themes.